2016
DOI: 10.1007/978-1-4939-3023-4_61
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Interactions in the Neurologically Compromised Neonatal Brain

Abstract: Neurological brain injuries such as hypoxic ischaemic encephalopathy (HIE) and associated conditions such as seizures have been associated with poor developmental outcome in neonates. Our limited knowledge of the neurological and cerebrovascular processes underlying seizures limits their diagnosis and timely treatment. Diffuse optical tomography (DOT) provides haemodynamic information in the form of changes in concentration of de/oxygenated haemoglobin, which can improve our understanding of seizures and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…A total of 11 clinical studies were identified [ 43 , 46 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], of which eight were case reports [ 43 , 46 , 75 , 77 , 78 , 79 , 80 , 82 ] and three were cohort studies [ 74 , 76 , 81 ]. The studies reported on NIRS parameters, HbO 2 , HHb, HbT, HbD, rSO 2 , FTOE and CCO.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 11 clinical studies were identified [ 43 , 46 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], of which eight were case reports [ 43 , 46 , 75 , 77 , 78 , 79 , 80 , 82 ] and three were cohort studies [ 74 , 76 , 81 ]. The studies reported on NIRS parameters, HbO 2 , HHb, HbT, HbD, rSO 2 , FTOE and CCO.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-ictal changes in cerebral haemodynamics were reported in four studies [ 43 , 46 , 80 , 82 ]. Singh et al [ 43 , 80 ] reported an increase in all haemoglobin parameters (HbO 2 , HHb and HbT) prior to the onset of seizures. These changes were reported as remarkably consistent between seizure events.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By using a structural prior to model field propagation within the head, imaging techniques such as DOT are enabled which produce images that spatially localise activation on the cortex (rather than relying on the position of sources and detectors on the scalp to interpret results, as is done in conventional fNIRS). In the last two decades, a large body of research applying DOT to the study of the neonatal brain has been established, such as studies of functional activation (Austin et al, 2006; Hebden, 2003; Karen et al, 2019; White, Liao, Ferradal, Inder, & Culver, 2012), neuropathology (Chalia et al, 2016; Dempsey et al, 2014; Plomgaard et al, 2016; Singh et al, 2016), and monitoring the brain for extended periods (Brigadoi et al, 2019). Previous work with infants has also employed prior structural information as a space to which functional data can be registered (Papademetriou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%